2020
DOI: 10.1111/jpn.13335
|View full text |Cite
|
Sign up to set email alerts
|

Dietary grape seed procyanidins suppressed weaning stress by improving antioxidant enzyme activity and mRNA expression in weanling piglets

Abstract: This study was conducted to investigate the effect of grape seed procyanidins (GSP) on growth performance, digestive enzyme activity, antioxidant enzyme activity and mRNA expression in weanling piglets. A total of 96 piglets (Pietrain × Large White) with an average initial body weight (BW) of 8.4 ± 1.7 kg were weaned at 28 days, and randomly divided into 4 groups. Four groups of animals were fed with a basic diet supplemented with various doses of GSP (0, 40, 70 and 100 mg/kg respectively) during the 28‐day tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
6
17
0
Order By: Relevance
“…Thus, we investigated the protective effect of RES on intestinal barrier function and the inflammatory response in DON-challenged piglets. As expected, our results showed that RES supplementation improved BW gain, ADG and gain/feed, which was in accordance with the findings of previous polyphenol-investigated studies [ 13 , 23 , 34 ]. Additionally, we observed that DON significantly impaired the growth performance of piglets, which was consistent with the results of previous studies [ 33 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, we investigated the protective effect of RES on intestinal barrier function and the inflammatory response in DON-challenged piglets. As expected, our results showed that RES supplementation improved BW gain, ADG and gain/feed, which was in accordance with the findings of previous polyphenol-investigated studies [ 13 , 23 , 34 ]. Additionally, we observed that DON significantly impaired the growth performance of piglets, which was consistent with the results of previous studies [ 33 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with these observations, our study showed that DON-challenged piglets exhibited elevated MDA levels and decreased GSH, T-SOD and T-AOC levels in the jejunum. Polyphenols have been shown to exert antioxidative effects in intestinal epithelial cell culture and weaned piglet studies [ 13 15 , 34 , 39 ]. Consistent with these findings, the results in the present study showed that supplementation with RES suppressed MDA levels while increasing T-SOD and T-AOC contents.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the appropriate concentrations of PCs improved the levels of antioxidant enzymes, including GSH-Px, CAT, and SOD, but decreased the levels of ROS and MDA in models of oxidative damage compared with measurements using H 2 O 2 alone. These present findings were consistent with previous studies which suggested that a low PCs supplement via diet can improve the activities of GSH-Px, CAT, and SOD in weaned piglets [ 30 ]. Another study also suggested that PCs significantly increased CAT and SOD activities and decreased MDA content, thus improving the quality of goat sperm [ 31 ].…”
Section: Discussionsupporting
confidence: 94%
“…In this study, compared with the MPP + /MPTP-alone group, PCs markedly raised the activity level of antioxidant enzymes (including GSH-Px, CAT and SOD) and decreased levels of ROS and MDA. The current findings are consistent with a previous study that suggests that a low PC supplement via diet improves the activities of GSH-Px, CAT and SOD in weaned piglets [40]. Another study also suggests that PCs significantly increase CAT and SOD activities and decrease MDA content, thus improving the quality of goat sperm [41].…”
Section: Discussionsupporting
confidence: 93%